A new 1, 2, 3-triazole-decorated imino-phenol: selective sensing of Zn2+, Cu2+ and picric acid under different experimental conditions. (3rd June 2021) - Ghosh, Sumit; Baildya, Nabajyoti; Ghosh, Kumaresh
Abstract : A new 1, 2, 3-triazole-based imino-phenol 1 is synthesized. It selectively senses Zn 2+ in CH3 CN–H2 O with a detection limit of 1.8 × 10 −6 M. Further, the selective sensing of Cu 2+ and picric acid is achieved by the ensemble 1 .Zn 2+ in CH3 CN–H2 O. Abstract : A new 1, 2, 3-triazole-decorated imino-phenol 1 has been synthesized, characterized and employed in metal ion sensing. Compound 1 is weakly fluorescent in CH3 CN–H2 O (3 : 1, v/v, pH = 6.8, and 10 mM HEPES buffer containing 1% DMSO) and shows substantial increase in emission upon interaction with Zn 2+ over a series of other metal ions. The binding constant ( K a ) and detection limit are evaluated as 9.06 × 10 4 M −1 and 1.8 × 10 −6 M, respectively. In the sensing of Zn 2+, Cu 2+ is observed to interfere and in reference to this, the selective sensing of Cu 2+ is achieved by the ensemble 1 .Zn 2+ in CH3 CN–H2 O (3 : 1, v/v, pH = 6.8, and 10 mM HEPES buffer containing 1% DMSO). As an application, the zinc-ensemble has been employed to detect picric acid (PA) over a series of other nitroaromatics. The experimental findings have been explained by a theoretical study using density functional theory.